Naravoslovne dejavnosti otrok v prostem času - vir izkustvenega znanja - Golob, Nika (Revija za elementarno izobraževanje, 2008)
The way of life in modern society often leads to the separation of people from nature and their environment. Therefore children often enter obligatory-level education without knowing how to properly connect to their environment. They have a great deal of theoretical knowledge but very little experience gained from the environment. In school, this division can become deeper if teachers do not pay enough attention to integrating experiential learning with environmental studies. If this integration can be achieved, by providing primary-level children with activities appropriate for their level of development, it would allow them to be capable of connecting learned knowledge with experience gained from the environment. We used the phenomenographic research method and a sample of 468 children to identify four categories of child-motivation for visiting an aquatic environment in their free time. The identified categories of conception mentioned above provided us with insight into the children's motivation. The results of our research can help build a foundation of new knowledge that can help increase our awareness of what motivates modern children.
Keywords: izkustveno znanje; naravoslovje; fenomenografsko raziskovanje; motivacija; motivation; prosti čas